Increased Association With Malnutrition and Malnourishment in Older Adults Admitted With Hip Fractures Who Have Cognitive Impairment and Delirium, as Assessed by 4AT. (23rd December 2020) - Han, Thang S.; Lisk, Radcliffe; Osmani, Ahmad; Sharmin, Rifat; El Gammel, Sarah; Yeong, Keefai; Fluck, David; Fry, Christopher H.
Abstract : Background: The Royal College of Physicians recently introduced the 4AT (Alertness, Abbreviated Mental Test‐4, Attention, and Acute change or fluctuating course) for screening cognitive impairment and delirium. Here, we examined the association of the 4AT with nutrition status in patients admitted to a hospital with hip fractures between January 1, 2016, and June 6, 2019. Methods: Nutrition status was assessed using the Malnutrition Universal Screening Tool, and the 4AT was assessed within 1 day after hip surgery. χ 2 Tests and logistic regression were conducted to assess the association of nutrition status with 4AT scores, adjusted for age and sex. Results: From 1082 patients aged 60–103 years, categorized into 4AT scores of 0, 1–3, or ≥4, the prevalence of malnutrition risk was 15.5%, 27.3%, and 39.6% and malnourishment was 4.1%, 13.2%, and 11.3%, respectively. Compared with the 4AT = 0 cohort, a 4AT score = 1–3 was associated with an increased malnutrition risk (odds ratio [OR], 2.3; 95% CI, 1.6–3.1) or malnourishment (OR, 3.6; 95% CI, 2.1–6.3). For a 4AT score ≥4, corresponding ORs were 4.0 (95% CI, 2.8–5.9) and 3.6 (95% CI, 1.9–6.8). Overall, there was a significant positive association: as 4AT scores increased, so did malnutrition risk. Conclusions: Among older adults admitted with hip fractures, high 4AT scores, which are suggestive of cognitive impairment and delirium, identified patients at increased malnutrition risk. These findings lend further support for the use of 4AT to identify patients who are at increased health risk.